A patent review of transient receptor potential vanilloid type 1 modulators (2014–present). (1st February 2021) - Gao, Mengkang; Wang, Yusui; Liu, Lanqi; Qiao, Zhenrui; Yan, Lin
ABSTRACT: Introduction : Transient receptor potential vanilloid 1 (TRPV1) is a nonselective cation channel with high permeability to calcium, which is widely expressed in the central nervous system (CNS) and peripheral nervous system. Since the TRPV1 was molecularly cloned more than 20 years ago, a series of research activities have been carried out on the possibility of new drugs. Areas covered : This review summarizes the patents on TRPV1 regulators (including agonists and antagonists) that were published during 2014–present and predicts the development direction in the future. The patent description is organized according to the applicant company and focuses on the representative compounds and their in vitro and in vivo data. Expert opinion : At present, TRPV1 is considered to be a molecular integrator of a broad range of chemical and physical stimuli. The desensitization of nociceptive neurons caused by TRPV1 agonists and the pharmacological blockade of TRPV1 by powerful small molecular antagonists are different treatments, both of which have analgesic effects. Unfortunately, TRPV1 modulators have suffered from adverse effects related to the role of TRPV1 channel in body temperature regulation and noxious heat sensation. What we need to know is whether these adverse effects are on-target (unavoidable), and whether chemical modification can be used to avoid or reduce these adverse reactions in the process of designing drug molecules, so as to develop a TRPV1 regulator with potent analgesic effect and no obvious adverse effects. Despite the difficulties and roadblocks, TRPV1 modulators remain powerful tools in pain research and represent promising therapeutic agents.